2021
DOI: 10.1016/j.radcr.2021.08.041
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine pancreatic tumor in a patient with dual diagnosis of tuberous sclerosis complex and basement membrane disease: A case report and review of the literature

Abstract: Tuberous Sclerosis is a complex genetic disease that has well-defined clinical criteria. These criteria don't include pancreatic neuroendocrine tumors. We represent a rare case of a patient, with a non–functioning pancreatic neuroendocrine tumor and concomitant diagnosis of tuberous sclerosis complex, and basement membrane disease. The patient was diagnosed based on typical radiologic findings. We have suggested close monitoring and during follow-up studies, the disease was stable. Interestingly the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…To the best of our knowledge, this is the first report of a dual TSC/KBG syndrome because of a single SV, even though dual diagnosis cases for TSC or KBG have already been reported. Kopadze et al (2021) have reported a clinical dual diagnosis case of TSC and basement membrane disease. They found two compound heterozygous variants in COL4A4 (p.Gly774Arg and p.Gly1465Asp) but no variant in either TSC1 or TSC2 .…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, this is the first report of a dual TSC/KBG syndrome because of a single SV, even though dual diagnosis cases for TSC or KBG have already been reported. Kopadze et al (2021) have reported a clinical dual diagnosis case of TSC and basement membrane disease. They found two compound heterozygous variants in COL4A4 (p.Gly774Arg and p.Gly1465Asp) but no variant in either TSC1 or TSC2 .…”
Section: Resultsmentioning
confidence: 99%
“…Neurocognitive disorders, especially seizures and intellectual disabilities, have historically been seen as hallmarks of TSC due to Vogt’s triad, but four of the reported patients demonstrated no neurocognitive impairment despite limited data, suggesting TSC may present without Vogt’s triad more frequently than once believed [ 37 , 41 , 43 , 45 , 53 ]. One report from 1984 describes a TSC patient with epilepsy who may have had concurrent PNET and RCC, both of which were found on autopsy [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…TSC2 mutations were found in 20 cases [ 16 , 17 , 19 , 27 , 34 37 , 40 , 44 , 47 , 51 ]. Nonfunctional PNET was found in 51 cases, 45 of which were found incidentally and the remaining six presented with abdominal/back pain secondary to mass effect [ 16 19 , 27 , 29 , 34 41 , 43 – 45 , 47 , 49 ]. Pediatric patients composed 26 cases [ 16 19 , 27 , 34 , 35 , 37 , 39 , 40 , 51 ].…”
Section: Discussionmentioning
confidence: 99%